NECS-based Cache Management in the Information Centric Networking - Fethellah, Nour El Houda; Bouziane, Hafida; Chouarfia, Abdallah (International Journal of Interactive Mobile Technologies (iJIM), 2021)
The Information Centric Networking ICN architectures are proposed to overcome the problems of the actual internet architecture. One of the main straight points of the ICN architectures is the in-network caching. The ICN performance is influenced by efficiency of the adopted caching strategy which manages the contents in the network and decides where caching them. However, the major issue which faces the caching strategies in the ICN architectures is the strategic election of the cache routers to store the data through its delivery path. This will reduce congestion, optimize the distance between the consumers and the required data furthermore improve latency and alleviate the viral load on the servers.  In this paper, we propose a new efficient caching strategy for the Named Data Networking architecture NDN named NECS which is the most promising architecture between all the ICN architectures. The proposed strategy reduces the traffic redundancy, eliminates the useless replication of contents and improves the replay time for users due to the strategic position of cache routers. Besides, we evaluate the performance of this proposed strategy and we compare it with three other NDN caching strategies, using the simulator network environment NdnSIM. On the basis of the simulations carried out, we obtained interesting and convincing results.